Oziotelphusa ganjamensis, a new species of freshwater crab (Brachyura: Gecarcinucidae) from south Odisha (Orissa) state, eastern India - Pati, S. K.; Sharma, R. M. (Zootaxa, 2012)
A new species of freshwater crab of the genus Oziotelphusa Müller, 1887 is described based on specimens collected froma rice field near Balakrushnapur, Ganjam district in Odisha (Orissa) state, eastern India. Oziotelphusa ganjamensis n. sp.is easily differentiated from its congeners by a distinct first gonopod (G1) having terminal segment bent outwards, whosetip is upturned and pointed, and subterminal segment relatively broad in the basal half to two-third portion and then sharply narrows to appear slender in distal half to two-third portion. A key to the Indian species of Oziotelphusa is also provided.